A Study of mathematical models and it applications - Singh, Anjali (Universal Research Reports, 2018)
A matrix is a set of integers arranged in a square. There are rows and columns in a matrix. A matrix's dimensions are determined by the number of rows and columns it contains. there are many kinds of rows and columns in matrices, as well as different types of null matrices, as well as different types of triangle matrices, as well as different sorts of antisymmetric matrices.